THE ANALYSIS OF BRAND EQUITY AND MARKETING MIX ON CUSTOMERS’ BUYING DECISION OF SOSRO TEA CONSUMERS LOCATED IN JAKARTA - Nabila Hilmy Zhafira; Tamitha Intassar Husen (universitas teuku umar, 2019)
The researcher would like to present a research regarding the analysis of brand equity and marketing mix on customers’ buying decision. Based on this research, researcher try to identify the influence between independent variables (marketing mix and brand equity) to dependent variable (customer buying decision). This research use primary and secondary data by survey method through distributing questionnaire and collected data from journals and books. This research used factor analysis to examined the data validity, and multiple regression model to testing the data using classic assumption test, such as: normality, multicollinearity, and heteroscedasticity tests. The classic assumption tests indicates that the available data have fulfill the condition to use multiregression model. The result shown that all those independent variables are at the same time (simultaneously) influence the dependent variable, and each of independent variable also has significance influence towards customer buying decision except place. The most significant influence comes from promotion and brand loyalty. At the end, researcher purpose not only for a better brand equity and marketing mix management, but also in order to setting better strategy for the company Keywords: Brand equity, Marketing mix, Buying decision